If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 3y + -9 = 0 Reorder the terms: -9 + 12x + 3y = 0 Solving -9 + 12x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 12x + 9 + 3y = 0 + 9 Reorder the terms: -9 + 9 + 12x + 3y = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 12x + 3y = 0 + 9 12x + 3y = 0 + 9 Combine like terms: 0 + 9 = 9 12x + 3y = 9 Add '-3y' to each side of the equation. 12x + 3y + -3y = 9 + -3y Combine like terms: 3y + -3y = 0 12x + 0 = 9 + -3y 12x = 9 + -3y Divide each side by '12'. x = 0.75 + -0.25y Simplifying x = 0.75 + -0.25y
| (6x+44)+(-10x+65)=180 | | 5x^(3/2)-25x^(1/2)+30x^(-1/2) | | 35x^6/7x^(1/4) | | 11+(-6)(3)= | | 3x+9=5x+10 | | 7x-10/4=-6 | | 0=2v-8 | | 22/2+(-6)(3) | | 5295/4.13 | | 8=-w+14 | | 7x-10/4=6 | | 3x-12x=4x+7x-16 | | 3(2z-7)=5z+17+2 | | 3x+4x-6=2 | | (22x+253)/30=11 | | (X/4)=23 | | c/2+3=-2 | | 18+x=51 | | 3y^2+15y=42 | | c/2+3-3=-2-3 | | 15y-14y+5=6 | | 5x-11=9-(4-14) | | 2r^3-3r^2=32r-48 | | 4x-9=24-3 | | 3/5x-10=-1 | | 4x-6(2x+3)=-2 | | 18.9=23.9 | | 36/60=45/x | | 37=32-2c | | 13.78-.8a=0 | | 16=8(x-1)-8 | | x/7-5/4=x/14-1/28 |